Analysis of dog fat in beef sausage using FTIR (Fourier Transform Infrared) combined with chemometrics - Any Guntarti; Zelinda Ayu Purbowati (Universitas Ahmad Dahlan, 2019)
Sausage is ready to eat meals for children and adults. The meat contained in a beef sausage might not be consistent to the one listed on the label. FTIR (Fourier Transform Infrared) spectroscopy combined with a chemometric method was the most used methods to detect beef fat with rapid and consistent results. Results of analysis can classify fatty acid composition. The aim of this study was to know the profile of spectra and grouping of beef tallow and dog meat with FTIR. The study was designed by making 7 different variations of dog reference sample concentrations (100%, 75%, 65%, 50%, 35%, 25%, and 100%) beef fat and five other samples were gathered from various street vendors. Results were analyzed using FTIR spectroscopy combined with chemometric with PLS (Partial Least Square) and PCA (Principal Component Analysis). The results of analysis will be analysed using Horizon MB application to obtained optimal wave number at 688-1124 cm-¹. Results equation obtained y = 0.9999 x + 0.0004 and value R² equal to 0.9999; RMSEC (root mean square error of calibration) of 0.30%; RMSEP (root mean square error of prediction) of 0.05% and RMSECV (root mean square error of cross validation) of 0.05%. The low values of RMSEP, RMSEC, RMSECV and R² close to one indicate that the FTIR combined with chemometric is an appropriate method for analyzing the presence of fat content in the sample. From the analysis showed that 1 of 5 sausage market samples has similarities with dog fat.